Professional know-how and MSD prevention: conceptual and methodological reflection leading to their identification and the start of their construction - Sylvie Ouellet; Nicole Vézina (Perspectives Interdisciplinaires sur le Travail et la Santé)
Repetitive work is often seen as work that can be learned by simple observation of a colleague. This study aimed to describe the know-how and especially the know-how that can be used for one’s protection, developed by six expert workers in a meat-cutting department. Individual and group interviews, on-site and video observations, and individual auto-confrontation (confronting participants with their own activity) were conducted. A typology of the know-how’s knowledge base was developed and the existence of a hierarchy in the development of expertise was brought to light, including know-how called « efficient know-how ». This hierarchy highlights all the complexity of the work that should be considered in organizing training and presenting content. The ergonomic approach developed in this study and a theoretical framework resulting from practice have helped to uncover the wealth of knowledge that is mobilized in manual labor.